The Effects of Patient Cost-Sharing on Adolescents' Healthcare Utilization and Financial Risk Protection: Evidence from South Korea - Seonghoon Kim; Kanghyock Koh; Wonjun Lyou (Institute of Labor Economics (IZA), 2024)
We examine the effects of patient cost-sharing on adolescents' healthcare utilization and out-of-pocket medical expenditures by exploiting the healthcare reform in South Korea that lowered the coinsurance rate for inpatient care from 20% to 5% for children under 16. We apply a difference-in-regression-discontinuities design using administrative claims data. We find that the reform increased adolescents' inpatient care utilization. It also reduced out-of-pocket healthcare expenditures. This effect was larger among low-income households, facilitating income redistribution. However, the lack of evidence on health improvements and household consumption spending responses suggests that generous patient cost-sharing for adolescent healthcare may cause efficiency losses.
Keywords: I12; I13; I18; 330; patient cost-sharing; healthcare utilization; out-of-pocket expenditure; income redistribution; consumption spending; difference in regression discontinuities design